Prevention of DoS attacks in VANET - Verma, K. (2013)
Privacy and Security have become an indispensable matter of attention in the Vehicular Ad-Hoc Network, which is vulnerable to many security threats these days. One of them is the Denial of Service (DoS) attacks, where a malicious node forges a large number of fake identities, i.e.; Internet Protocol (IP) addresses in order to disrupt the proper functioning of fair data transfer between two fast-moving vehicles. In this paper, a distributed and robust approach is presented to defend against DoS attacks. In this proposed scheme, the fake identities of malicious vehicles are analyzed with the help of consistent existing IP address information. Beacon packets are exchanged periodically by all the vehicles to announce their presence and to become aware of the next node. Each node periodically keeps a record of its database by exchanging the information in its environment. If some nodes observe that they have similar IP addresses in the database, these similar IP addresses are identified as DoS attacks. However, it can be expected that security attacks are likely to increase in the coming future due to more and more wireless applications being developed onto the well-known exposed nature of the wireless medium. In this respect, the network availability is exposed to many types of attacks. A DoS attack on the network availability is being elaborated in this paper. A model of a product interaction for DoS prevention has been developed called "IP-CHOCK" that will lead to the prevention of DoS attacks. The proposed approach will be able to locate malicious nodes without the requirement of any secret information exchange and special hardware support. Simulation results demonstrate that the detection rate increases when optimal numbers of nodes are forged by the attackers. Â© 2013 Springer Science+Business Media New York.